POWER QUALITY IMPROVEMENT TECHNIQUES IN HYBRID SYSTEMS – A REVIEW (International Journal of Engineering and Computer Science, 2014)
Power Quality is one of a major constraint in power system transmission and distribution. Now a day’s most of the energy was consumed by us. The abnormal growth of Electric Energy consumers, power demand is also being increased. At the same time the unavailability of fossil fuels and the cost of generation, transmission and utilization are increased. Hence, the power producer opposes to reduce the cost of power generation. Simultaneously the consumer thinks about that, to get good quality of power and to minimize the power tariff. To meet the both ends we go for hybrid power generation system. To implement Hybrid power system, it has several problems such as Protection, Synchronization, Power Quality, etc., in this paper we focused on various methods of power quality improvement Techniques in hybrid power systems.